2010
DOI: 10.4236/ns.2010.28105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biotechnological potential of phosphate solubilizing bacteria isolated from soils of Southern Kazakhstan

Abstract: Phosphorus (P) is a vital plant nutrient, available to plant roots only in soluble forms that are in short supply in the soil. Adding phosphate- based fertilizers to increase agricultural yields is a widely used practice; however, the bio- availability of P remains low due to chemical transformations of P into insoluble forms. Thus, phosphate solubilizing bacteria (PSB) play an important role in reducing P deficiency in soil. The goal of this study was to assess biotechnological potential of phosphate-solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Table 4. Relaxation time (τ•10 12 sec), dispersion amplitudes ( ∆ , ∆ ) and weighting factors according to equations ( 12)-( 13) and ( 14)-( Taken as initial values, the dispersion parameters of pure components were subject to slight variation [19,20]. The final selection of parameters was determined by the minima of the sum of the root-mean-square deviations of the coefficients calculated using these equations (𝜀 , 𝜀 " ) from the measured ones (ε′, ε″):…”
Section: Eejp 1 (2024)mentioning
confidence: 99%
“…Table 4. Relaxation time (τ•10 12 sec), dispersion amplitudes ( ∆ , ∆ ) and weighting factors according to equations ( 12)-( 13) and ( 14)-( Taken as initial values, the dispersion parameters of pure components were subject to slight variation [19,20]. The final selection of parameters was determined by the minima of the sum of the root-mean-square deviations of the coefficients calculated using these equations (𝜀 , 𝜀 " ) from the measured ones (ε′, ε″):…”
Section: Eejp 1 (2024)mentioning
confidence: 99%
“…Among the individual inoculants inoculation treatment T 6 (75% RDF + Isolate II) shows maximum chlorophyll a content followed by T 5 (75% RDF + Isolate I), T 4 (75% RDF + AM Fungi) and Reference strain showing chlorophyll a content of 1.79 mg/g, 1.71 mg/g, 1.66 mg/g and 1.59 mg/g respectively (Fig 3). [3] they studied and reported that inoculation with PSB significantly enhanced root length and radicle length of wheat as compared to the individuals. This could be due to the release of plant growth promoting substances by inoculants.…”
Section: Growth Parametersmentioning
confidence: 99%
“…(Khan, et al, 2009). Thus, phosphate solubilizing bacteria (PSB) play an important role in reducing P deficiency in soil (Aipova, et al, 2010).and have attracted the attention of agriculturalists as soil inoculums to improve the plant growth and yield (Fasim, et al, 2002). It has provided their worth as biological alternative to compensate agrochemicals and to sustain environment-friendly crop production (Dobbelaere, et al, 2003).…”
Section: Introductionmentioning
confidence: 99%